PENGARUH SOSIAL MEDIA MARKETING, KUALITAS PRODUK, DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI TOKO KOPI TUKU - Muhammad Rayhan Aditari (2022)
This type of research conducted by researchers is a quantitative study that aims to determine the effect of social media marketing, product quality, and product prices on purchasing decisions. This study used a sample of 100 respondents from the population in Greater Jakarta who had made purchases at the Tuku Coffee Shop at least once. The sampling technique uses non-probability sampling using purposive sampling method. The data collection carried out in this study used an online questionnaire using the Google Form which was then distributed via the Line, WhatsApp, Twitter, Instagram and Telegram applications. This study uses the PLS (Partial Least Square) analysis technique with the SmartPLS 3.0 application. The results obtained from this study are: (1) Social media marketing variables have a positive and significant effect on purchasing decisions with an original sample value of 0.454. (2) The product quality variable has a positive and significant effect on purchasing decisions with an original sample value of 0.229. (3) The product price variable has a positive and significant effect on purchasing decisions with an original sample value of 0.294